Field notes contributed by Peter C. Petersen, spring 1997 - Petersen, Peter C.et al (1997)
List of birds and locations contributed by Peter C. Petersen with observers Kelly McKay, Brian Blevins, Walter Zuurdeeg and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed/flatbed